Partnering for change (P4C) in Sweden- a study protocol of a collaborative school-based service delivery model to create inclusive learning environments - Vedrana B. Baric; Moa Yngve; Marie Holmefur; Inna Feldman; Jenny Wilder; Kine Johansen; Nina Klang; Helene Lidström; Maria Borgestig (BMC, 2023)
Abstract Background Inclusive learning environments are considered as crucial for children's engagement with learning and participation in school. Partnering for change (P4C) is a collaborative school-based service delivery model where services are provided at three levels of intensity based on children's needs (class, group-, individual interventions). Interventions in P4C are provided universally to support all children with learning, not only children with special education needs (SEN), and as such are expected to be health-promoting. Aim The aim of the study is to evaluate the effectiveness and cost-effectiveness of P4C as well as school staff members' and children's experiences after P4C. Methods In a parallel, non-randomised controlled intervention design, 400 children, aged 6-12 years, and their teachers, will be recruited to either intervention classes, working according to the P4C, or to control classes (allocation ratio 1:1). Data will be collected at baseline, post-intervention (4 months), and 11 months follow-up post baseline. The primary outcome is children's engagement with learning in school. Secondary outcomes include for example children's health-related quality of life and wellbeing, occupational performance in school, attendance, and special educational needs. The difference-in-differences method using regression modelling will be applied to evaluate any potential changes following P4C. Focus group interviews focusing on children, and professionals' experiences will be performed after P4C. A health economic evaluation of P4C will be performed, both in the short term (post intervention) and the long term (11-month follow-up). This study will provide knowledge about the effectiveness of P4C on children's engagement with learning, mental health, and wellbeing, when creating inclusive learning environments using a combination of class-, group- and individual-level interventions. Trial registration number NCT05435937.